Goal-directed aimed movements with path obstructions - Hoffmann, Errol R.; Sheikh, Ilyas H. (Ergonomics, 2012)
Studies are reported in which participants moved from a starting position to a final target, but moved around obstacles that prevented a direct path being taken. Seven experiments are reported in which subjects made multiple-component movements, defined by changes in the direction of movement, but without intervening targets (or stopping points) between components. It was found that components of movement time did not interact, contrary to the results of Gan and Hoffmann ( 1988b ) for cases where there was an intervening target, and that component times could be added. For ballistic components, the time for the movement was linearly related to the square root of the total amplitude of movement; for components that were visually controlled, the time was related to Fitts' Index of Difficulty based on the total amplitude of movement and the final target size. Results are compared to data for movements with intervening targets, where the movement integration hypothesis is valid. Practitioner Summary: Many movements, particularly to inaccessible places, cannot be made directly, but must be made about obstacles in the path. This research shows how times for these movements can be quantified in terms of the direct path length and the size and location of the obstacles.